RESPONSE TO INTERVENTION - Al Otaiba, Stephanie; Wanzek, Jeanne; Yovanoff, Paul (European Scientific Journal, ESJ, 2015)
The purpose of this interdisciplinary paper is to describe Response to Intervention (RTI), or multi-tier systems of support, for early literacy to improve reading outcomes for students with or at risk for reading disability. First we review the current US policy on RTI for the purpose of early literacy intervention and for identification of reading disabilities. We situate this within recent efforts in developing countries supported by the World Bank and the Early Grade Reading Assessments. Then, we highlight a large experimental study we conducted with first graders and provide findings from a third grade follow up. We conclude with implications for research, practice, and policy.